Design of photovoltaic/thermal (PV/T) with heat pipes as a heat transfer medium used for water heater - Rahmat Iman Mainil; Afdhal Kurniawan Mainil; Azridjal Aziz; Faisal Afif (Politeknik Negeri Lhokseumawe, 2023)
One of the main obstacles for developers and users of photovoltaic (PV) modules is that the module temperature is too high due to high solar radiation and a higher ambient temperature, which reduces PV efficiency. A photovoltaic/thermal (PV/T) system is a technique developed for absorbing heat, that combines PV with a solar thermal collector (STC). In this research, heat pipes are used as the heat transfer medium. This paper aims to design a PV/T system for water heating and examines the thermal performance and water temperature that can be achieved by PV/T. In designing PV/T, the method used is to estimate the intensity of solar radiation and determine the size of the thermal collector, thermal insulation, type of working fluid, and heat pipe filling ratio. The PV/T thermal performance is also tested after the system design has been built. The design parameters that have been obtained are the PV area of 0.67 m2 and the volume of heated water of 20 liters. This design proposes water as the working fluid of the heat pipe with a filling ratio of 10%. The system performance indicates that PV/T could heat the water to 50.9 °C with energy absorbed by the water of 1.85 MJ, and the maximum thermal efficiency of PV/T is 27.14%. The results show that PV/T has a very promising future in terms of its ability to use heat energy and can be further developed for future research so that it can encourage people to use environmentally friendly renewable energy